The effect of social media marketing on brand trust and brand loyalty for hotels - ERDOĞMUŞ, ZEYNEP İREM (SPRINGER HEIDELBERG, 2016)
Web 2.0 as a personalized and communicative form of Internet technology is an essential tool for firms to improve their online marketing skills. In the context of this study, hotels are chosen as an exemplary field since it is one of the key leading economic sectors in Turkey. Building and maintaining brand loyalty and trust are the important themes for every firm in such competitive environment. Hotels, in this case, have made many efforts on branding to gain brand loyalty and brand trust from their customers and recently they have carried their efforts to social media to survive in online environment as well. But, in general hotels are booked via mediators like Booking. com etc., thus hotels' own websites are not visited as an online store. The aim of this study is to identify the effect of social media marketing efforts on brand loyalty and brand trust for hotels, especially on hotels' own websites. The effect of social media marketing efforts including (1) a clear website, (2) website security, (3) active and updated social media tools, (4) online interactivity and (5) collaboration with other useful websites on brand loyalty and trust were tested by using structural equations model. The results show the positive effects of a clear website, website security, online interactivity and collaboration with other useful websites on brand trust and the effect of brand trust on brand loyalty. The study is believed to be helpful to marketing managers of the hotels in terms of protecting their own online stores and meet their visitors first at their own websites. Also, crafting right online strategies to compete with other hotels and mediators is an important aim. The results of the study is believed to add to the extant literature in terms of social media marketing.
Keywords: Hotels; Social media marketing; Brand loyalty; Brand trust; WEB 2.0; IMPACT; TOOL; USABILITY; TOURISM; WEBSITE; EQUITY